2021
DOI: 10.1177/0960327121991911
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiles of transient receptor potential (TRP) channels in the peripheral blood mononuclear cells of psoriasis patients

Abstract: Psoriasis is a chronic autoimmune disease in which peripheral blood mononuclear cells (PBMCs) are involved in the pathological process. Transient receptor potential (TRP) channels expressed in immune cells have been shown to be associated with inflammatory diseases. We aimed to evaluate mRNA expression levels of TRP channels in PBMCs of patients with psoriasis. 30 patients with plaque psoriasis and 30 healthy age- and gender-matched control subjects were included in this study. mRNA expression levels of TRP ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 39 publications
(48 reference statements)
1
10
0
Order By: Relevance
“…In our previous study, TRPV3 gene expression was decreased in PBMCs of psoriasis patients. 32 Similarly, in this study, the TRPV3 mRNA expression was lower in RRMS patients when compared to that of healthy individuals.…”
Section: S408supporting
confidence: 66%
“…In our previous study, TRPV3 gene expression was decreased in PBMCs of psoriasis patients. 32 Similarly, in this study, the TRPV3 mRNA expression was lower in RRMS patients when compared to that of healthy individuals.…”
Section: S408supporting
confidence: 66%
“…Previous study reported the expression levels of TRPC6 channel on mRNA and protein levels are significantly reduced both in cultured psoriatic keratinocytes and psoriasis plaques (30). Recently, other group detected mRNA expression levels of TRP channels in PBMCs of 30 patients with psoriasis, data showed that in the patient group, the TRPC6 expression levels were lower compared to controls (31). We have also used the data in the GEO database to perform differential gene analysis to clarify the exact changes of mRNA levels of TRPC6 channels in psoriasis skin lesions.…”
Section: Discussionmentioning
confidence: 93%
“…Ozcan, S.S. et al reported that TRP channels expressed in immune cells have been shown to be associated with inflammatory diseases [ 52 ]. TRPM4, TRPM7, TRPV3, TRPV4 , and TRPC6 mRNA expression levels in peripheral blood mononuclear cells (PBMCs) of patients with PS were investigated.…”
Section: Mechanisms Of Trpv3 Channel Activation In Pruritusmentioning
confidence: 99%